2015
DOI: 10.1021/ac5039362
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-MS-Based Quantitative Analysis for Ketone Containing Homoserine Lactones in Pseudomonas aeruginosa

Abstract: N-Acyl homoserine lactones (AHLs), quorum sensing molecules produced by Gram-negative bacteria, are used as important secondary metabolites for antibacterial drug development and cell-to-cell communication. Although various analytical techniques have been developed for detection and quantitation of AHLs from more complex bacterial culture media, only a few methods have been applied to AHL identification in physiological samples. Here, we developed a highly sensitive and reliable MALDI-based 3-oxo AHL quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Besides, the embedding matrix required for MALDI analysis substantially limits its ability to study lower molecular weight compounds because of the presence of high matrix signal below the mass over charge ratio ( m/z ) 1000. Quorum sensing molecules (QSMs) 11 and rhamnolipids 12 have previously been detected using MALDI-ToF, but these methods required extraction from bacterial cultures and a chemical derivatisation or labelling step.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the embedding matrix required for MALDI analysis substantially limits its ability to study lower molecular weight compounds because of the presence of high matrix signal below the mass over charge ratio ( m/z ) 1000. Quorum sensing molecules (QSMs) 11 and rhamnolipids 12 have previously been detected using MALDI-ToF, but these methods required extraction from bacterial cultures and a chemical derivatisation or labelling step.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has reported MALDI-MS-based quantitative analysis of carbohydrates and bioactive lipids ( e.g ., N-acyl homoserine lactones) that have an aldehyde or ketone group 34 35 36 . Previous studies have demonstrated that chemical derivatization of the target molecules could dramatically enhance the sensitivity (up to 6 × 10 4 times) and allow more accurate quantitative analysis using only MALDI-MS without prior sample purification 36 . In this study, we expand the application to steroid hormones for the practical use of MALDI-MS in the quantitative analysis of targeted biomolecules.…”
Section: Resultsmentioning
confidence: 99%
“…High Performance Liquid Chromatography (HPLC) (Poonguzhali et al, 2007), Liquid Chromatography coupled with Mass Spectrometry (LC-MS) (Middleton et al, 2002), High Performance Liquid Chromatography coupled with Mass Spectrometry (HPLC-MS) (Liu et al, 2017), Liquid Chromatography coupled with tandem Mass Spectrometry (LC-MS/MS) (Ortori et al, 2011), Gas Chromatography coupled with Mass Spectrometry (GC-MS) (Cataldi et al, 2007), Matrix Assisted Laser Desorption Ionisation Mass Spectrometry (MALDI-MS) (Kim et al, 2015), Nuclear Magnetic Resonance Spectroscopy (NMR) (Kumar et al, 2016) and Fourier Transform Infrared Spectroscopy (FTIR) (Taghadosi et al, 2015) have been explored for detection of AHLs from cell-free supernatants of gram negative bacterial cultures. Although, these detection techniques have achieved remarkable sensitivities in AHL quantification, they often require extensive sample pre-treatment and/or molecular derivatization steps as prerequisites for the analysis.…”
Section: Ahl Detection: State-of-the-artmentioning
confidence: 99%